P72 Incidental Detection Of Early Stage Non-small Cell Lung Cancer – Time To Implement Screening?. (10th November 2014) - Thakrar, RM; Brown, JM; Brazil, SV; Nankivell, M; Lawrence, DR; George, PJ; Janes, SM; Navani, N
Abstract : Introduction: Early detection is the key to survival in non-small cell lung cancer (NSCLC) where surgical resection can be undertaken. However, stage I and II disease combined account for only 25–30% of patients presenting with lung cancer. Although, clinical pathways from primary care exist to facilitate expeditious management of patients, the role of other referral pathways to diagnosis of surgically treatable lung cancers is not known. Methods: Patients suitable for surgical resection for curative intent for primary lung cancer were identified between 2007 and 2011 at this institution. Patients diagnosed 'incidentally' on radiology were compared to those detected through the standard 'two week' wait target referral system. Specific data on demographics, diagnostics utilised, pathological stage, and lung cancer mortality were recorded. Results: Eighty-four patients were treated with surgical resection for non-small cell cancer. The 'two-week' wait referrals accounted for one quarter (n = 21; 95% CI 17–35%) of the all the referrals, whilst 61% (n = 51; 95% CI 50–70%) of patients were found to have lung cancer detected incidentally through investigations performed by other specialties in the hospital. The presentation of patients to hospital with cancer related symptoms whether they had operable disease or not, had significantly higher lung cancer specific mortality (p = 0.02; see figure ). Conclusion: We demonstrate that patients who have cancer-related symptoms have a worse outlook. Whilst asymptomatic patients diagnosed by chance have better prospects for cure by surgical resection, thus highlighting the promise of CT screening for lung cancer in patients with high risk factors.